1997
DOI: 10.1006/bcon.1997.0508
|View full text |Cite
|
Sign up to set email alerts
|

Gene Flow in the Exotic Colonizing LadybeetleHarmonia axyridisin North America

Abstract: Gene flow was studied inHarmonia axyridis(Pallas) (Coleoptera: Coccinellidae), an exotic, arboreal ladybeetle predator that recently spread rapidly throughout North America. A survey of isozyme polymorphisms showed 30 of 52 resolved putative loci were polymorphic (58%), and the mean heterozygosity was 16.75 ± 2.98% among all loci and 26.31 ± 4.37% at only the polymorphic loci. The mean number of alleles at the 52 loci was 2.01 ± 1.97. Gene frequencies were estimated in populations from Georgia, Virginia, Delaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…We conjecture that the arrival of H. axyridis in Oregon in 1991 resulted from accidental or intentional releases, not from its unaided dispersal from the southeastern U.S.A. For instance, this predator was commercially available as a biological control agent in North America (Heimpel & Lundgren 2000) and was intentionally redistributed within the continent for biological control purposes, with well documented intentional movement of H. axyridis from the southeastern U.S.A. to California and New Mexico, U.S.A in 1992 and 1993 and Texas, U.S.A. in 1994 (Tedders & Schaefer 1994). It is interesting to note that the extensive spread of H. axyridis in North America has occurred despite relatively narrow genetic differentiation of the invading populations (Krafsur et al 1997).…”
Section: Invasion Historymentioning
confidence: 99%
See 1 more Smart Citation
“…We conjecture that the arrival of H. axyridis in Oregon in 1991 resulted from accidental or intentional releases, not from its unaided dispersal from the southeastern U.S.A. For instance, this predator was commercially available as a biological control agent in North America (Heimpel & Lundgren 2000) and was intentionally redistributed within the continent for biological control purposes, with well documented intentional movement of H. axyridis from the southeastern U.S.A. to California and New Mexico, U.S.A in 1992 and 1993 and Texas, U.S.A. in 1994 (Tedders & Schaefer 1994). It is interesting to note that the extensive spread of H. axyridis in North America has occurred despite relatively narrow genetic differentiation of the invading populations (Krafsur et al 1997).…”
Section: Invasion Historymentioning
confidence: 99%
“…the succinea group appears to predominate throughout North America (Chapin & Brou 1991;Tedders & Schaefer 1994;Dreistadt et al 1995;Kidd et al 1995;LaMana & Miller 1996;Hesler et al 2001Hesler et al , 2004Wise et al 2001) even though initial colonies of this insect maintained by the United States Department of Agriculture contained the succinea and melanic groups (Krafsur et al 1997) and both groups were available commercially (e.g., Koch et al 2004b).…”
Section: Invasion Historymentioning
confidence: 99%
“…In 1988 and 1991, the first detections of H. axyridis were made in Louisiana and Georgia, hundreds of kilometers from their release sites (Chapin & Brou, 1991;Tedders & Schaefer, 1994). Thereafter, H. axyridis rapidly spread in North America and is now found throughout the United States and Canada (Coderre et al, 1995;Dreistadt et al, 1995;LaMana & Miller, 1996;Nalepa et al, 1996;Krafsur et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated genetic diversities and gene flow in the foregoing Palearctic species (Krafsur & Obrycki, 1996;Krafsur et al, 1992Krafsur et al, , 1996aKrafsur et al, , 1997. In addition, we quantified genetic diversity in the ladybird species, Adalia bipunctata L. and Coleomegilla maculata Degeer (Krafsur et al, , 1996b, and added diversity esti-mates for the Neotropical Eriopis connexa Germar and the Palearctic Scymnus frontalis (F.) coccinellids.…”
Section: Introductionmentioning
confidence: 99%
“…Despite releases in fourteen US states 45 between 1964and 1982(Gordon 1985, H. axyridis was not reported as established in the 46 country until 1988 (Chapin and Brou 1991). There is uncertainty over the source of the 47 established US population, which may originate from a single intentional release or 48 accidental introduction (Krafsur et al 1997). Day et al (1994) suggested that the source 49 could have been accidental seaport introductions.…”
Section: U N C O R R E C T E D P R O O F 39mentioning
confidence: 99%